Mg2+-derived mesoporous ultra-high silica twelve-membered-ring basic zeolites: straightforward synthesis and catalytic performance. Issue 7 (25th January 2016) - Xie, Jingyan; Wen, Haimeng; Zhang, Wei; Zhou, Yu; Wang, Jun
Abstract : Mg 2+ -derived ultra-high silica mesoporous zeolites are synthesized by acidic pre-co-hydrolysis/condensation and act as an efficient zeolitic solid base in Knoevenagel condensations. Abstract : Mg 2+ -derived mesoporous ultra-high silica twelve-membered-ring zeolites with multiple topologies (MOR, BEA and MTW) were straightforwardly synthesized by a one-pot route, where the crucial step was the co-hydrolysis/condensation of silica source and magnesium salt under moderate acidic conditions. SiO2 /Al2 O3 ratios can be adjusted from ∼30 to as high as 410, thus generating superior basicity that was further improved by the incorporation of Mg species. A mesoporous structure was self-formed without the assistance of any template or special strategy. Catalysis tests showed high activity of these zeolites in a typical base reaction, Knoevenagel condensation, even for the bulky substrates due to the enhanced mass transfer arising from the mesopores. This methodology provides a promising approach towards target synthesis of valuable Mg 2+ -derived mesoporous ultra-high silica zeolites with tunable acid/base properties, which can even act as an efficient mesoporous zeolitic solid base.